Pembuatan Rumah Pangan Lestari di Desa Midang Making of Sustainable Food Houses in Midang Village - Fahruddin Fahruddin; Fortuna Syahna Syaqillah (Unram Journal of Community Service, 2021)
Food is anything that comes from biological sources and water, either processed or unprocessed, which is intended as food or drink for human consumption. This includes food additives, food raw materials, and other materials used in the preparation, processing and or manufacture of food or beverages. This food is very attached to the theme we are currently taking, namely "Sustainable Food Homes. Just like the theme we took, we finally built a sustainable food house in Midang Hamlet, Midang Village, Gunung Sari District. In making sustainable food houses, we are also assisted by local residents ranging from men or women, both young and old. We obtained land in Midang Hamlet which is also one of the lands leased by the village to be managed by POKDARWIS (Tourism Awareness Group). The purpose of making this sustainable food house is to optimize the existing land as a place for providing food for the local community. So that people can consume vegetables and some other food for free, easy and close. In addition to the POKDARWIS area, we also socialize with local people to take advantage of their respective yards. Besides being able to optimize their house yards, they can also save more for certain costs. Sambal builds a sustainable food house and does not forget that we also do counseling or presentations on plant care, nurseries and so on. So that local residents have knowledge about plant care and do not forget we also invite residents to carry out joint planting and distribution of planting seeds that they shared previously so that they can be taken home and cared for privately in their respective homes.